From problem people to addictive products: a qualitative study on rethinking gambling policy from the perspective of lived experience - Helen E. Miller; Samantha L. Thomas; Priscilla Robinson (BMC, 2018)
Abstract Background Previous research has shown that government and industry discussions of gambling may focus on personal responsibility for gambling harm. In Australia, these discussions have largely excluded people with lived experience of problem gambling, including those involved in peer support and advocacy. Methods We conducted 26 in-depth interviews with people with current or previous problem gambling on electronic gaming machines (EGMs) involved in peer support and advocacy activities, using an approach informed by Interpretive Policy Analysis and Constructivist Grounded Theory. Results Participants perceived that government and industry discussed gambling as safe and entertaining with a focus on personal responsibility for problem gambling. This focus on personal responsibility was perceived to increase stigma associated with problem gambling. In contrast, they described gambling as risky, addictive and harmful, with problem gambling resulting from the design of EGMs. As a result of their different perspectives, participants proposed different interventions to reduce gambling harm, including reducing accessibility and making products safer. Conclusions Challenging the discourses used by governments and industry to describe gambling, using the lived experience of people with experience of gambling harm, may result in reduced stigma associated with problem gambling, and more effective public policy approaches to reducing harm.